2021
DOI: 10.1055/s-0041-1739543
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Dentoskeletal Changes of the Twin Block Appliance and the AdvanSync2 Appliance in Treatment of Skeletal Class-II Malocclusion in Pakistani Population: A Randomized Clinical Trial

Abstract: Objective This study aimed to compare dentoskeletal changes in skeletal class-II malocclusion with removable twin block appliance and fixed AdvanSync2 appliance. Materials and Methods A prospective randomized clinical trial was conducted over a span of 1 year at AFID at Rawalpindi. Thirty patients with skeletal class-II malocclusion, 16 males (53.3%) and 14 females (46.6%), were randomly selected and divided in two equal groups (15 each) to be treated with either fixed functional appliances (FFAs) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The former study presents with a low risk of bias but the latter presents with a high risk of selection bias thereby more care should be taken to avoid this for future studies. 15,16 Lastly comparing the original Herbst appliance to its modification which is the Advansync TM appliance in a randomized control trial, Kaushik et al 17 have reported that there was a significant increase in the mandibular length as well as a reduction of the total overjet. In both these parameters, the Herbst appliance produced better results as compared to the Advansync TM appliance although the latter produced significant lower incisor proclination.…”
Section: Discussionmentioning
confidence: 99%
“…The former study presents with a low risk of bias but the latter presents with a high risk of selection bias thereby more care should be taken to avoid this for future studies. 15,16 Lastly comparing the original Herbst appliance to its modification which is the Advansync TM appliance in a randomized control trial, Kaushik et al 17 have reported that there was a significant increase in the mandibular length as well as a reduction of the total overjet. In both these parameters, the Herbst appliance produced better results as compared to the Advansync TM appliance although the latter produced significant lower incisor proclination.…”
Section: Discussionmentioning
confidence: 99%
“…Class II malocclusion, a complex orthodontic issue, is characterized by a convex facial profile due to maxillary retrusion, mandibular protrusion, or both [ 1 ]. Approximately one in three individuals suffer from Class II malocclusion [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The retarded mandible may cause the backward displacement of the tongue and hyoid bone, resulting in constriction of the upper airway (UA), which is one of the causative factors for the development of obstructive sleep apnea (OSA) syndrome [1,4] . As functional appliances, the Twin-Block appliances with maxillary expander are used at an early stage to wide the maxillary arch, release the retracted mandible, balance the muscles and beautify the facial pro le to a certain extent [5] . With the improved anteroposterior relation between maxilla and mandible, the tongue and hyoid bone following move forward, which may increase the volume of the UA theoretically [4,6] and be gradually concerned by orthodontists.…”
Section: Introductionmentioning
confidence: 99%